FRONTEX (EUROPEAN BORDER AND COAST GUARD AGENCY) SECURITIZATION AGENDA IN GREECE ILLEGAL IMMIGRANTS - Lestari, Putri; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Illegal immigrants are persons or groups entering a country without meeting the legal requirements to enter the country or without completing the necessary documents and permits. The entry of illegal immigrants in Greece left a negative impact on politics, socio-culture and security. Illegal immigrants travel very dangerous trip in order to realize their desires. Economic and security factors are the main reason people or groups travel far from their homes even beyond obstacles that are dangerous to their safety. Seeing the rampant flow of illegal immigrants, many pose a threat both in transit countries and in destination countries. Therefore, there needs to be an effort that can deal with the problem of illegal immigrants. The method used by the authors in this study is the level of group behavior analysis. The level of group behavior analysis assumes that the main focus is on studying the behavior of groups and organizations involved in relationships. Data collection techniques in this study through literature study (library reaserch) and interview techniques (field study). The author uses it to obtain the necessary information by reading, understanding, comparing and analyzing books, scientific journals, articles and other data. The arrival of illegal immigrants includes a new threat to the Greece society in this case the Greece Government is trying to do the handling by conducting securitization process in cooperation with FRONTEX (European Border And Coast Guard Agency),where FRONTEX make preventive and curative efforts. These efforts include supervision, maintenance and cooperation with other international organizations. Keywords: Illegal Immigrant, Greece, Securitization, Frontex